2022
DOI: 10.1186/s41983-022-00525-2
|View full text |Cite
|
Sign up to set email alerts
|

Neuroinflammation in autism spectrum disorders: potential target for mesenchymal stem cell-based therapy

Abstract: Background Autism spectrum disorders (ASD) include a group of neurodevelopmental disorders characterised by repetitive behaviours and impairments in communication, emotional and social skills. This review gives an overview of ASD, focusing on the aetiological and clinical aspects. It also discusses the role of neuroinflammation in ASD, critically examines the current evidence on the therapeutic effects of MSCs in ASD and consolidates key findings in this area of research. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 81 publications
0
22
0
Order By: Relevance
“…Since its first description in a series of 11 children by Leo Kanner 80 years ago (1), ASD is being more frequently diagnosed, so that its estimated direct and indirect economic costs in the USA will likely reach the 500 billion USD mark in 2025, making this pathology more costly than diabetes (2).…”
Section: Introductionmentioning
confidence: 99%
“…Since its first description in a series of 11 children by Leo Kanner 80 years ago (1), ASD is being more frequently diagnosed, so that its estimated direct and indirect economic costs in the USA will likely reach the 500 billion USD mark in 2025, making this pathology more costly than diabetes (2).…”
Section: Introductionmentioning
confidence: 99%
“…Although neuroinflammation in ASD has become more prominent in studies, it is not yet clear whether neuroinflammation causes ASD or is a consequence of ASD (Wong 2022). One study showed that individuals with ASD had active neuroinflammation in the cortex, white matter and cerebellum, with simultaneous activation of astrocytes and microglia (Vargas et al 2005).…”
Section: Neuroinflammation In Asdmentioning
confidence: 99%
“…Several meta-analyses have confirmed a strong involvement of neuroinflammatory processes in practically all neuropsychiatric and/or neurodegenerative diseases including ASD [2,[35][36][37][38][39][40][41][42][43][44]. Thus, it has been reported that individuals with ASD have significantly higher levels of several inflammatory biomarkers, including tumor necrosis factor-alpha (TNF-α), interleukin-1 beta (IL-1β), and C-reactive protein (CRP) compared to healthy controls [37].…”
Section: Neuroinflammation In Asdmentioning
confidence: 99%
“…As mentioned earlier, no cure for ASD is yet available. However, research in this area and potential use of anti-inflammatory drugs and antioxidants as well as mesenchymal stem cell-based therapy have been suggested [40,44]. Recently, involvement of the histaminergic system and potential therapeutic exploitation of this system in ASD and other conditions associated with impairment in executive functioning was provided [39].…”
Section: Neuroinflammation In Asdmentioning
confidence: 99%